2014
DOI: 10.4103/0974-7796.127018
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon causes of anterior urethral diverticula in children: Two cases and review of literature

Abstract: Anterior urethral diverticula are rare in children. Anterior urethral valves and associated diverticulum is the commonly discussed pathological entity in children. There is a lack of awareness among clinicians regarding less common presentations of anterior urethral diverticula in children; which can have a diverse involvement of the urinary tract. This report describes two uncommon presentations of anterior urethral diverticula in children, their diagnoses and management. A systematic differential diagnosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Opacification was not possible in the part of the urethra beyond the diverticulum, probably due to the valve-like mechanism of the distal lip of the diverticulum. Voiding Cysto Urethro Graphy (VCUG), which provides a more accurate assessment of CAUD than MCUG, has shown that the obstructing distal lip forms an acute angle with the urethra [9,10]. Sono-urethrography or voiding ultrasound is a non-invasive alternative to conventional imaging studies that use a contrast medium [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opacification was not possible in the part of the urethra beyond the diverticulum, probably due to the valve-like mechanism of the distal lip of the diverticulum. Voiding Cysto Urethro Graphy (VCUG), which provides a more accurate assessment of CAUD than MCUG, has shown that the obstructing distal lip forms an acute angle with the urethra [9,10]. Sono-urethrography or voiding ultrasound is a non-invasive alternative to conventional imaging studies that use a contrast medium [3].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between these two pathologies, however, is controversial, with some authors considering these two conditions as being on the same continuum while others have distinguished between the two conditions [1,6,7,9]. AUV is characterised by presence of a valve on cystourethroscopy, with dilation of the proximal urethra, forming an obtuse angle with the ventral floor of the urethra on VCUG [9,10]. Specifically, for our patient who presented a CAUD with a distal penile location, congenital megalourethra was another differential diagnosis to consider, defined as an anterior urethral anomaly due to aplasia of the erectile bodies [9].…”
Section: The Main Differential Diagnosis Of Caud Is Anteriormentioning
confidence: 99%
“…Congenital anterior urethral diverticulum may be found all along the anterior urethra, but is usually located between the bulbous and the mid-penile urethra, mostly on the ventral surface and in the anterior urethra with diameter typically between 3 and 5 cm. [14][15][16][17] The embryology remains unclear. No family pattern of inheritance has been detected yet.…”
Section: Discussionmentioning
confidence: 99%
“…This approach may provide a more uniform caliber of urethra, but there is a risk of urethrocutaneous fistula formation. 5,17,18 Quoraishi et al 32 adopted an endoscopic approach with incision of the lip of the diverticulum. However, these patients can again develop a flap, requiring repeat procedures.…”
Section: Ijrsmsmentioning
confidence: 99%
“…In the index case, the most probable reason for posterior urethral diverticulum would have been the urinary catheterization during the postnatal period in the initial days of life. Few cases of congenital anterior urethral diverticulum have been reported in the pediatric population (6,7). Affected patients usually present either with urinary obstruction or as UTI (8), although few reports show its varied presentation of midline prostatic cyst (9) and need differentiation from the paraurethral cyst (10).…”
Section: Discussionmentioning
confidence: 99%